Glucokinase Deficit Prevalence in Women With Diabetes in Pregnancy: A Matter of Screening Selection - Bitterman, Olimpia; Giuliani, Chiara; Festa, Camilla; Napoli, Angela (Frontiers in Endocrinology, 2020)
Introduction: The prevalence among pregnant women with diabetes of monogenic diabetes due to glucochinase deficit (GCK-MODY) varies from 0 to 80% in different studies, based on the chosen selection criteria for genetic test. New pregnancy-specific Screening Criteria (NSC), validated on an anglo-celtic pregnant cohort, have been proposed and include pre-pregnancy BMI <25 Kg/m2 and fasting glycemia >99 mg/dl. Our aim was to estimate the prevalence of GCK-MODY and to evaluate the diagnostic performance of NSC in our population of women with diabetes in pregnancy. Patients and methods: we retrospectively selected from our database of 468 diabetic pregnant patients in Sant’Andrea Hospital, in Rome, from 2010 to 2018, all the women who received a genetic test for GCK deficit because of specific clinical features. We estimated the prevalence of GCK-MODY among tested women and the minimum prevalence in our entire population with not autoimmune diabetes. We evaluated diagnostic performance of NSC on the tested cohort and estimated the eligibility to genetic test based on NSC in the entire population. Results: 409 patients had diabetes in pregnancy, excluding those with autoimmune diabetes; 21 patients have been tested for GCK-MODY, 8 been positive and 13 negative (2 of them had HNF1-alfa mutations and 1 had HNF4-alfa mutation). We found no significant differences in clinical features between positive and negative groups except for fasting glycemia, higher in the positive group. The minimum prevalence of monogenic diabetes in our population was 2.4%. The minimum prevalence of GCK-MODY was 1.95%. In the tested cohort the prevalence of GCK-MODY was 38%. In this group NSC sensitivity is 87% and specificity 30%, positive predictive value is 43% and negative predictive value 80%. Applying NSC on the entire population of women with not autoimmune diabetes in pregnancy, 41 patients (10%) would be eligible for genetic test; considering a fasting glycemia >92 mg/dl, 85 patients (20.7%) would be eligible. Discussion: In our population, NSC have good sensitivity but low specificity, probably because there are many GDM with GCK-MODY like features. It is mandatory to define selective criteria with a good diagnostic performance on Italian population, to avoid unnecessary genetic tests.